Lack of Association between LCS6 Variant in KRAS Gene with the Occurrence of Breast Tumors in Iraqi Women (Baghdad Science Journal, 2020)
Breast cancer is the most commonly diagnosed cancer and remains one of the main reasons of cancer-related mortality in women worldwide. KRAS variant rs61764370 (T>G) is associated with an increased risk of occurrence of many cancers, Here The case-control study was accomplished on 135 women including 45 women with breast cancer patients, 45 women with benign breast lesions and 45 healthy women to analyze the association of KRAS variant rs (61764370 T>G) with breast cancer. LCS 6 variant in KRAS gene was amplified by using specific primers, then genotype was detected after sequencing the PCR products. The results showed that the genotype and allele frequency of TT and GT allele of KRAS gene were statistically non-significant (p< 0.01) among breast cancer patients and breast benign lesions compared with healthy controls in Iraqi women.